Tuberculous Osteomyelitis of the Hyoid Bone: A Case Report - Paul Emerson; Ajay Philip; George M. Varghese; Regi Thomas (Case Reports in Otolaryngology)
Skeletal tuberculosis is a well-known disease entity. We report the first case involving hyoid bone and the use of polymerase chain reaction-based test in detection and management. A 62-year-old male presented with neck swelling of a 20-day duration along with change of voice and dysphagia. Examination revealed a cystic, osteolytic lesion of the hyoid bone which histopathologically demonstrated features of granulomatous infection. A polymerase chain reaction test confirmed the diagnosis of tuberculosis.